Dual Axis Solar Tracker System Application Based on Arduino Atmega 2560 and Internet of Things (iot) for Submersible Pump Operation - Wahyono, Wahyono; Suwarti, Suwarti; H, Yusuf Dewantoro; Citraningtyas, Dita Putri; Ardiansyah, Muhammad Ridho; Cahyani, Regita Fitri; Prihartini, Retno; Pangestu, Wisnu (Eksergi, 2022)
Most of the Solar Power Plants (PLTS) still use a static system which is considered less effective in absorbing solar energy. This is due to the earth's rotation which causes the sun to not always be in the same position. In order to optimize the absorption of solar energy so that the power produced is stable and maximum, a tracking system is applied to the solar panels. This tool works by using 4 LDR sensors and 2 DC Power Window motors as the driving force and the presence of Wi-Fi as a communication medium between the Arduino ATmega 2560 and the Android application so that the performance of the solar tracker can be monitored via a smartphone in real time. The purpose of this research is to optimize the efficiency of solar panels. The method used in this research is Research and Development (R&D). The test was carried out with the Dual Axis Solar Tracker system against a load in the form of a submersible pump. The test results show the average efficiency of the Dual Axis Solar Tracker system is 20.89% with an average power output of 84.81%.